Pengaruh Kebijakan Dividen, Kepemilikan Manajerial, Kepemilikan Institusional, Dan Ukuran Perusahaan Terhadap Nilai Perusahaan: Studi Kasus Perusahaan Sektor Manufaktur dalam Indeks Kompas-100 Terdaftar Di BEI 2017-2022 - Qurotul A’yunina; Rizka Ariyanti (Lokawati : Jurnal Penelitian Manajemen dan Inovasi Riset, 2023)
This study investigates how dividend policy, management ownership, company size, and institutional ownership affect company value. This research aims to study how dividend policy, management ownership, company size, and institutional ownership influence company value partially and simultaneously. Secondary data from annual reports was used for this research. The population used is manufacturing companies listed on the Indonesia Stock Exchange (BEI) in the Kompas100 index from 2017 to 2022. 6 companies from the 22 population companies are the sample selected using the purposive sampling method. Multiple linear regression analysis was carried out using the SPSS 25 statistical program. This research found that dividend policy partially had a negative effect on Company Value (PBV), manager ownership had a partial positive effect on Company Value (PBV), company size had no partial and negative effect. on Company Value (PBV), and institutional ownership partially has a positive effect on Company Value (PBV). This research finds that the independent variables dividend policy, manager ownership, company size, and institutional ownership influence the dependent variable Company Value (PBV) simultaneously.